Some can whistle a novel - McMurtry, Larry 1936-2021 (Simon and Schuster, 1989)
Danny Deck, a middle-aged Texas writer, finds his peaceful life overturned by the arrival of T.R., the daughter he has never seen, her two children, and her two lovers--Muddy, a failed cat burglar, and Earl Dee, a dangerous psychopath.
Keywords: Fathers and daughters -- Fiction; Love stories.; Television writers -- Fiction; Thalia (Tex. : Imaginary place) -- Fiction; Texas -- Fiction; Love stories